Improve employee performance with job satisfaction and organizational commitment - Abdika Rizki, Akang; Madhadi, Madhadi; Robiyana, Robiyana; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
Effective management, thinking about the importance of human resources. Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 50 respondents drawn into samples using non-probability sampling using saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that job satisfaction significantly influences employee performance. The second hypothesis states that organizational commitment significantly affects employee performance. The third hypothesis is that employee performance is influenced by job satisfaction and corporate loyalty, which can simultaneously improve employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.